l-Citrulline Protects from Kidney Damage in Type 1 Diabetic Mice - Romero, Maritza J.; Yao, Lin; Sridhar, Supriya; Bhatta, Anil; Dou, Huijuan; Ramesh, Ganesan; Brands, Michael W.; Pollock, David M.; Caldwell, Ruth B.; Cederbaum, Stephen D.; Head, C Alvin; Bagi, Zsolt; et al. (Frontiers in Immunology, 2013)
Rationale: Diabetic nephropathy (DN) is a major cause of end-stage renal disease, associated with endothelial dysfunction. Chronic supplementation of l-arginine (l-arg), the substrate for endothelial nitric oxide synthase (eNOS), failed to improve vascular function. l-Citrulline (l-cit) supplementation not only increases l-arg synthesis, but also inhibits cytosolic arginase I, a competitor of eNOS for the use of l-arg, in the vasculature. Aims: To investigate whether l-cit treatment reduces DN in streptozotocin (STZ)-induced type 1 diabetes (T1D) in mice and rats and to study its effects on arginase II (ArgII) function, the main renal isoform. Methods: STZ-C57BL6 mice received l-cit or vehicle supplemented in the drinking water. For comparative analysis, diabetic ArgII knock out mice and l-cit-treated STZ-rats were evaluated. Results:l-Citrulline exerted protective effects in kidneys of STZ-rats, and markedly reduced urinary albumin excretion, tubulo-interstitial fibrosis, and kidney hypertrophy, observed in untreated diabetic mice. Intriguingly, l-cit treatment was accompanied by a sustained elevation of tubular ArgII at 16 weeks and significantly enhanced plasma levels of the anti-inflammatory cytokine IL-10. Diabetic ArgII knock out mice showed greater blood urea nitrogen levels, hypertrophy, and dilated tubules than diabetic wild type (WT) mice. Despite a marked reduction in collagen deposition in ArgII knock out mice, their albuminuria was not significantly different from diabetic WT animals. l-Cit also restored nitric oxide/reactive oxygen species balance and barrier function in high glucose-treated monolayers of human glomerular endothelial cells. Moreover, l-cit also has the ability to establish an anti-inflammatory profile, characterized by increased IL-10 and reduced IL-1β and IL-12(p70) generation in the human proximal tubular cells. Conclusion:l-Citrulline supplementation established an anti-inflammatory profile and significantly preserved the nephron function during T1D.